2023
DOI: 10.2196/44922
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Social Media Use Interventions on Mental Well-Being: Systematic Review

Abstract: Background There is some evidence that more social media use is related to poorer mental well-being and that social media use can become problematic when it starts to interfere with a person’s daily life and mental well-being. To address this issue and improve users’ mental well-being, social media use interventions (eg, abstinence from social media) have been developed and evaluated. However, there is limited understanding of the effectiveness of these interventions in improving mental well-being.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 75 publications
0
7
0
Order By: Relevance
“…Scott et al (2019) [ 38 ] also suggested a possible link with sleep disturbance, which was similarly more prevalent among our cohort. The findings reported to date lend themselves to discussions around the development and evaluation of interventions to address problematic digital technology use in clinical youth populations, of which there is some evidence of effectiveness [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…Scott et al (2019) [ 38 ] also suggested a possible link with sleep disturbance, which was similarly more prevalent among our cohort. The findings reported to date lend themselves to discussions around the development and evaluation of interventions to address problematic digital technology use in clinical youth populations, of which there is some evidence of effectiveness [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to this, there is an acknowledgement with the improvements in technology, for example, better broadband and network capabilities, that the internet can be a valuable self-help resource for those living with depression. A review by Plackett et al (2023) found evidence of a reduction in depressive symptoms when using social media interventions alongside therapy-based interventions such as cognitive behavioural therapy (CBT). The National Institute for Health and Clinical Excellence (NICE) in the UK, which produce evidence-based guidelines, recommend online cognitive behavioural therapy (CBT) for those with mild depression (NICE, 2004).…”
Section: Behavioural Intervention Technologiesmentioning
confidence: 99%
“…In addition to this, there is an acknowledgement with the improvements in technology, for example, better broadband and network capabilities, that the internet can be a valuable self-help resource for those living with depression. A review by Plackett et al. (2023) found evidence of a reduction in depressive symptoms when using social media interventions alongside therapy-based interventions such as cognitive behavioural therapy (CBT).…”
Section: Behavioural Intervention Technologiesmentioning
confidence: 99%
“…As the difference between virtual and real identities increases, it becomes difficult for individuals to have high expectations of themselves. Consequently, this conflict may cause dislike of the self and result in depression [ 51 ]. Therefore, considering the negative consequences of preferences in creating virtual identities, it is important to examine social network identity management.…”
Section: Introductionmentioning
confidence: 99%